Long term outcome in patients with silent versus symptomatic ischaemia during dobutamine stress echocardiography. Issue 6 (13th May 2005) - Biagini, E; Schinkel, A F L; Bax, J J; Rizzello, V; van Domburg, R T; Krenning, B J; Bountioukos, M; Pedone, C; Vourvouri, E C; Rapezzi, C; Branzi, A; Roelandt, J R T C; et al.
Abstract : Objectives: To compare the long term prognosis of patients having silent versus symptomatic ischaemia during dobutamine stress echocardiography (DSE). Design: Observational study. Setting: Tertiary referral centre. Patients: 931 patients who experienced stress induced myocardial ischaemia during DSE. Results: Silent ischaemia was present in 643 of 931 patients (69%). The number of dysfunctional segments at rest (mean (SD) 9.6 (5.1) v 8.8 (5.0), p  =  0.1) and of ischaemic segments (3.5 (2.2) v 3.8 (2.1), p  =  0.2) was comparable in both groups. During a mean (SD) follow up of 5.5 (3.3) years, there were 169 (18%) cardiac deaths and 86 (9%) non-fatal infarctions. Multivariable Cox regression analysis showed age (hazard ratio (HR) 1.1, 95% confidence interval (CI) 1.02 to 1.05), previous myocardial infarction (HR 1.4, 95% CI 1.1 to 2.0), and number of ischaemic segments during the test (HR 2.0, 95% CI 1.0 to 3.7) as independent predictors of cardiac death and myocardial infarction. For every additional ischaemic segment there was a twofold increment in risk of late cardiac events. The annual cardiac death or myocardial infarction rate was 3.0% in patients with symptomatic ischaemia and 4.6% in patients with silent ischaemia (p < 0.01). Silent induced ischaemia was an independent predictor of cardiac death and myocardial infarction (HR 1.7, 95% CI 1.1 to 2.0). During follow up symptomatic patients were treated more often with cardioprotective therapy (p < 0.01) and coronary revascularisation (145 of 288 (50%) v 174 of 643 (27%), p < 0.001). Conclusions: Patients with silent ischaemia had a similar extent of myocardial ischaemia during DSE compared to patients with symptomatic ischaemia but received less cardioprotective treatment and coronary revascularisation and experienced a higher cardiac event rate.